Ergonomic analysis of the shaping post in the injection sector of a footwear industry - Costa, Sofia (2015)
The footwear industry has risk factors associated with the development of musculoskeletal disorders. The objective of tire study was to perform an ergonomic analysis at the workstation of shaping, in the injection sector of a footwear industry, using the technique Ergonomic Workplace Analysis (EWA). The results allowed the selection of the risk factors requiring intervention: posture, repetitivity and force application. The most demanding tasks were selected for the application of two methods: Strain Index (SI) and Rapid Upper Limb Assessment (RULA). The SI application revealed that the tasks have serious risks of musculoskeletal disorders and the RULA application showed the need of immediate intervention for the task of shaping and soon intervention for hammering. The assessment provided by the two methods can be used in a complementary way to estimate the risk. The introduction of mechanical aids in “shaping” may contribute to a safer task.